Niche differentiation among comammox (Nitrospira inopinata) and other metabolically distinct nitrifiers - Yang, Xueqin; Yu, Xiaoli; He, Qiang; Deng, Ting; Guan, Xiaotong; Lian, Yingli; Xu, Kui; Shu, Longfei; Wang, Cheng; Yan, Qingyun; Yang, Yuchun; Wu, Bo; et al. (Frontiers in Microbiology, 2022)
Due to global change, increasing nutrient input to ecosystems dramatically affects the nitrogen cycle, especially the nitrification process. Nitrifiers including ammonia-oxidizing archaea (AOAs), ammonia-oxidizing bacteria (AOBs), nitrite-oxidizing bacteria (NOBs), and recently discovered complete ammonia oxidizers (comammoxs) perform nitrification individually or in a community. However, much remains to be learned about their niche differentiation, coexistence, and interactions among those metabolically distinct nitrifiers. Here, we used synthetic microbial ecology approaches to construct synthetic nitrifying communities (SNCs) with different combinations of Nitrospira inopinata as comammox, Nitrososphaera gargensis as AOA, Nitrosomonas communis as AOB, and Nitrospira moscoviensis as NOB. Our results showed that niche differentiation and potential interactions among those metabolically distinct nitrifiers were determined by their kinetic characteristics. The dominant species shifted from N. inopinata to N. communis in the N4 community (with all four types of nitrifiers) as ammonium concentrations increased, which could be well explained by the kinetic difference in ammonia affinity, specific growth rate, and substrate tolerance of nitrifiers in the SNCs. In addition, a conceptual model was developed to infer niche differentiation and possible interactions among the four types of nitrifiers. This study advances our understanding of niche differentiation and provides new strategies to further study their interactions among the four types of nitrifiers.